Effect of Temperature on Microstructure, Hardness, and Tensile Strength of Al Alloy Cast Iron - Oktavianus, Yosep; Ratna Kartikasari,; Mustakim, (ReTII, 2023)
This research aims to study the effect of tempering temperature on the microstructure, hardness and tensile strength of Al alloy cast iron. The tempering process carried out includes a hardening process at a temperature of 900oC for 1 hour followed by cooling in the water medium. The next stage is tempering which is carried out at temperatures of 200ºC, 250ºC, 300ºC, 350ºC, and 400ºC for 1 hour followed by cooling in air media. The tests carried out were chemical composition tests using a spectrometer, microstructure tests using an optical microscope, hardness using the Vickers method, and tensile tests. The chemical composition test results show that the main element content is Fe 92.24%, the main alloying element Al 1.36%, and C 3.49%, the microstructure of the alloy consists of ferrite, pearlite, and graphite, after the hardening process the ferrite phase appears dominant because the Al element acts as a former and stabilizer of the ferrite phase, while the tempering process shows that the pearlite phase is evenly distributed along with the ferrite phase between the graphite flakes which turns smaller. Al alloy cast iron has a hardness value of 186.16 kg/mm2, after the tempering process the hardness decreases to a minimum of 125.14 kg/mm2 at a temperature of 400oC. The tensile test results showed that there was a decrease in tensile stress after the hardening process of 94.61 Mpa, whereas after the tempering process, the tensile stress experienced an irregular increase and decrease.